Role of PI3K/AKT Signaling Pathway in Nucleus Pulposus Cells. (2nd July 2021) - Xiao, Quan; Teng, Yun; Xu, Changming; Pan, Wei; Yang, Hanshi; Zhao, Jiali; Zhou, Quan
Abstract : Objective . To investigate the role of PI3K/AKT signaling pathway in nucleus pulposus (NP) cells. Methods . Nucleus pulposus (NP) cells were isolated from SD rat, and thereafter, passage three (P3) NP cells were divided into the following experimental groups: control, PI3K/AKT agonist IGF-1 (25 ng/ml, 50 ng/ml, and 100 ng/ml), and PI3K/AKT inhibitor LY294002 (5 μ M, 10 μ M, and 20 μ M). Flow cytometry and BrdU cell proliferation assays were performed to assess apoptosis and the proliferation rate of NP cells. Western blot analysis was performed to examine the protein expression level of Col II, Col X, Aggrecan, and MMP13. Results . PI3K/AKT inhibitor LY294002 increased the rate of apoptosis in NP cells when compared to the control and decreased the proliferation rate when compared to control. Moreover, LY294002 decreased the protein expression level of Col-II and Aggrecan in NP cells. At the same time, LY294002 increased the protein expression level of MMP13 and Col-X in NP cells. Through activating PI3K/AKT, IGF-1 increased the proliferation rate when compared to control and decreased the rate of apoptosis when compared to control. Additionally, IGF-1 decreased the protein expression level of MMP13 and Col-X and increased Col-II and Aggrecan in NP cells. Conclusion . The inhibition of PI3K/AKT signaling pathway accelerated the apoptosis of NP cells and facilitated the extracellular matrix degradation. However, the activation of PI3K/AKT pathway partly prevented the NP cell from apoptosis and promoted their proliferation. Meanwhile, its activation also delayed the loss of extracellular matrix.